FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI BATIK BASUREK DI KOTA BENGKULU PROVINSI BENGKULU - Wulan Dari, Ponda Tiara; Novrita, Sri Zulfia; Nelmira, Weni (Journal of Home Economics and Tourism, 2017)
Many factors that affect production batik basurek of batik industry in thecity of Bengkulu. Among them was caused by the supply of raw materials has notbeen efficient, the lack of a competent workforce, and the high cost ofproduction/capital in batik. The aimed of this research was to describe whetherthere is influence of the raw materials, labor, and cost of production of batikbasurek against capital in the city of Bengkulu province of Bengkulu. The type ofresearch that is quantitative descriptive, with the entire population of industryleader batik basurek, as many as six people. The number of samples is equal tothe number of population. The technique of sampling using the technique saturated of sampling. Engineering data collection using the likert scale withquestion form distributed to respondents and have tested the validity andreliability. The results showed: 1) inventories raw materials are located on bothcategories of 50.00%. 2) amount and quality of labor with very high requirement,low and very low each of 33,33%. 3) availability of production cost/very highcapital of 66,66%. 4) the quality and number of batik production with a very highrequirement, low and very low each of 33,33%). Based on multiple regressionanalysis, hypothesis testing and the results of the determination of the coefficientindicates that the raw material (X1), labor (X2), and cost of production/capital(X3), has a positive influence and significantly to the production of batik basurekamounted to 99.8%.Keywords: Batik basurek production, the city of Bengkulu.